Discrimination Depicting Disrespect - Peden, Blaine F.; Walkowlak, Nicholas J.; Van Cleave, Austin M. (My University, 2018)
Discrimination is unjust treatment of others. Discrimination is commonly directed toward minority groups such as different ethnicities and sexualities (Bahns & Branscombe, 2011). Discrimination can be active or subtle. Subtle acts include staring at and avoiding of the community. The Campus Climate Survey showed that a majority of the LGBT community feels unsafe on campus (Bronstead-Bruns & Goodman, 2015). Anecdotal observations noted participants avoiding LGBT displays at prior CERCA poster sessions. We report a naturalistic observation on glaring and avoiding on the UWEC campus. We expected more frequent glaring and avoiding by individuals moving past the Bridge relative to the Math Lab.
Color poster with text and graphs.
Keywords: College safety; Discrimination; LGBT; Posters